Characteristics of TiN coating deposited by vacuum-arc method on rotating cylindrical sample - Kalinichenko, A.I.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2019)
The dependences of the growth rate and intrinsic stress on the accelerating potential for coating TiN deposited from the Ti⁺ ion flow on the surface of cylindrical article are investigated theoretically. The sample rotates around the symmetry axis perpendicular to the flow of incident ions. The study is carried out within the framework of the model of the nonlocal thermoelastic peak of the low-energy ion, taking into account the sputtering of the coating atoms. The cases of the DC mode and the pulsed potential mode are considered. It is shown that the intrinsic stress in the coating TiN to be deposited on the rotating cylinder are ~ 20 % less than in the coating deposited on the flat substrate located perpendicular to the incident ion flow.